2012
DOI: 10.1186/1745-6215-13-118
|View full text |Cite
|
Sign up to set email alerts
|

Duration of luteal support (DOLS) with progesterone pessaries to improve the success rates in assisted conception: study protocol for a randomized controlled trial

Abstract: BackgroundLuteal support with progesterone is necessary for successful implantation of the embryo following egg collection and embryo transfer in an in-vitro fertilization (IVF) cycle. Progesterone has been used for as little as 2 weeks and for as long as 12 weeks of gestation. The optimal length of treatment is unresolved at present and it remains unclear how long to treat women receiving luteal supplementation.DesignThe trial is a prospective, randomized, double-blind, placebo-controlled trial to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Whilst we concede that the emerging evidence suggests that early withdrawal of luteal support is safe and would signifi cantly reduce unnecessary treatment burden and drug costs for patients, larger prospective well designed trials are required before this can be adopted as routine practice. At least one randomised placebo-controlled trial studying the effect of luteal support duration is registered with the ISRCTN database (Gazvani et al, 2012). In the meantime, the inconsistencies observed in practice are likely to continue.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst we concede that the emerging evidence suggests that early withdrawal of luteal support is safe and would signifi cantly reduce unnecessary treatment burden and drug costs for patients, larger prospective well designed trials are required before this can be adopted as routine practice. At least one randomised placebo-controlled trial studying the effect of luteal support duration is registered with the ISRCTN database (Gazvani et al, 2012). In the meantime, the inconsistencies observed in practice are likely to continue.…”
Section: Resultsmentioning
confidence: 99%
“…The other described a retrospective analysis and so did not meet inclusion criteria (Schmidt et al, 2001). After literature search and screening, seven articles remained for inclusion in the analysis (Aboulghar et al, 2008;Gazvani et al, 2012;Goudge et al, 2010;Kohls et al, 2012, Kyrou et al, 2011Nyboe Andersen et al, 2002, Prietl et al, 1992.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Three of the trials were identified as having high-risk allocation concealment (Kohls et al, 2012;Nyboe Andersen et al, 2002;Prietl et al, 1992) indicating concern of possible selection bias due to inadequate concealment of allocations. Only one of the trials adequately blinded participants, personnel and outcome assessors; this was also the only placebo-controlled trial (Gazvani et al, 2012). A summary of Week 4 (day 15 after OR) 55…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations